(untitled) (Revista cientifica In Vestigium Ire, 2016)
This article deals with matters relating to the “ Country Brand - The answer is Colombia “ , from what this strategy of the Government, until the moment it is possible to determine in what way can the Boyacenses Employers use this brand to position its products in the Turkish market.